2020
DOI: 10.1002/jpln.201900045
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus application alters concentrations and proportions of organic Se forms in the grain of winter wheat

Abstract: A deficiency or excess of selenium (Se) can cause disease in the human body, and the dietary intake of organic forms of Se is considered the preferable way to satisfy the Se demand in humans. P application decreases Se uptake and thus also Se concentrations in grains of crops, but little is known about how the P application level may affect the organic forms of Se in the grain of winter wheat. A pot trial with three P levels (0, 80, and 160 mg P kg -1 soil) and three Se levels (0, 0.5, and 1 mg Se kg -1 soil) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, the influence of P application on Se uptake and accumulation in plants depends on the rate of the P application (Liu et al, 2018;Li et al, 2019b). Nie et al (2020) also demonstrated that all Se fractions (total, organic, inorganic) in the grain of winter wheat were significantly decreased under increasing P application rates. Therefore, in agricultural production, it is very important to avoid excessive use of P fertilizer, so that a balance is achieved between higher yield and appropriate grain Se concentration.…”
Section: The Role Of Phosphorus In the Regulation Of Se Bioavailabilimentioning
confidence: 90%
“…In addition, the influence of P application on Se uptake and accumulation in plants depends on the rate of the P application (Liu et al, 2018;Li et al, 2019b). Nie et al (2020) also demonstrated that all Se fractions (total, organic, inorganic) in the grain of winter wheat were significantly decreased under increasing P application rates. Therefore, in agricultural production, it is very important to avoid excessive use of P fertilizer, so that a balance is achieved between higher yield and appropriate grain Se concentration.…”
Section: The Role Of Phosphorus In the Regulation Of Se Bioavailabilimentioning
confidence: 90%
“…According to the method of Nie et al [ 105 ], approximately 0.5 g of plant samples (shoot or root) was digested with HNO 3 -HClO 4 (4:1) at 180 °C. The digest was then restored to volume with 6 mol·L −1 HCl, cooled, filtered and brought to volume with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Soil proteases mainly hydrolyze organic N to amino acids and are a source of N for higher plants (Nie et al . 2020). N‐acetamide glucose ribosidase and asparaginase catalyse protein and peptide metabolism (Patra et al .…”
Section: Resultsmentioning
confidence: 99%
“…Soil urease is a highly specific enzyme that promotes the hydrolysis of urea to ammonium N for plant uptake and utilization (Fisher et al 2017). Soil proteases mainly hydrolyze organic N to amino acids and are a source of N for higher plants (Nie et al 2020). N-acetamide glucose ribosidase and asparaginase catalyse protein and peptide metabolism (Patra et al 2017).…”
Section: Effects Of Different Fertilizers and Soil Ph On Soil Enzyme ...mentioning
confidence: 99%